Review on Regulation of Microglia after Spinal Cord Injury through Physical Therapy - ZHAI Chenyuan; WU Qi; CAI Jili; WANG Yu; WANG Zun; FANG Lu; WANG Tong (康复学报)
Spinal cord injury (SCI) is a devastating central nervous system condition caused by factors such as trauma, tumors, or inflammation that lead to the destruction of the integrity and continuity of the spinal cord, resulting in severe sensory, motor, and autonomic dysfunction. Microglia, as inherent immune cells in the central nervous system, play an extremely important role in neuroimmune responses after SCI and are the most significantly changing cell population in terms of space and time after SCI. Therefore, clarifying the spatiotemporal changes of microglia after spinal cord injury has great significance for finding effective intervention strategies for spinal cord injury rehabilitation. In recent years, studies on regulating the function and state of microglia through physiotherapy to promote functional recovery after SCI have been gradually increasing. This paper reviews the spatial and temporal changes of microglia after SCI and the research progress of physiotherapy in regulating microglia, aiming to provide a more effective therapeutic strategy for physiotherapy to improve the function of SCI.